S, Se and Te contents of basalts from the Reykjanes Ridge and SW Iceland Rift Zone - Forrest, Allison; Schilling, Jean-Guy; Kelley, Katherine (IEDA: EarthChem Library, 2017)
Abstract: This data set reports S, Se, and Te concentrations in basaltic whole-rocks and glasses from the SW Iceland rift zone, including sub-glacial glasses, and submarine lavas from the Reykjanes Ridge, Gibbs Fracture Zone, and Mid-Atlantic Ridge. We thank R. Kingsley, J.M. Rhodes, and C. Mandeville for assistance with analyses. This work was supported by NSF award OCE# 0326658 to JGS. NSF award OCE# 1555523 provides curatorial support for marine geological samples at the Graduate School of Oceanography, University of Rhode Island. Other Description: Forrest, A. (2005), Sulfur, Selenium and Tellurium in Reykjanes Ridge and Iceland Basalts, 175 pp, University of Rhode Island, Kingston, RI. Forrest, A., R. Kingsley, and J.-G. Schilling (2009), Determination of Selenium and Tellurium in Basalt Rock Reference Materials by Isotope Dilution Hydride Generation-Inductively Coupled Plasma-Mass Spectrometry (ID-HG-ICP-MS), Geostandards and Geoanalytical Research, 33(2), 261-269, doi:10.1111/j.1751-908X.2009.00841.x.